Wizerunek samorządu terytorialnego w prasie lokalnej - Wierzbicki, Artur (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
The Author discusses the image of local government emerging from Polish local press, especially in those locations where several titles exist (and continue to operate). For the purpose of the paper two weeklies were selected and analyzed: „Głos Wągrowiecki” and „Tygodnik Wągrowiecki” which have the highest circulation and reach in the Wągrowiec area (powiat). The analysis is based on a sample covering all the issues between July 2002 and June 2003.